THEORETICAL FOUNDATIONS OF CALCULATING THE SYSTEM FOR THE ORGANIC FERTILIZERS INTRODUCTION IN SUCTION PIPELINES OF PUMPING STATIONS FOR FERTILIZING IRRIGATION AGRICULTURAL CROPS - Vladimir A. Rudakov; Dmitriy V. Maklakov; Sergey A. Tarasyants; Yulia S. Urzhumova (Мелиорация и гидротехника, 2023)
Purpose: to substantiate theoretically the calculation of the system for introducing organic fertilizers into the suction pipelines of pumping stations during fertilizing irrigation of agricultural crops. Materials and methods. The foundations of calculating the system of introducing organic fertilizers into the suction pipelines of pumping stations during fertilizing irrigation are developed on the basis of literary sources and authors’ research. If there is a composition of nutrients in the manure of cattle (CM), horse, pig or sheep for the planned harvest of the adopted crop, the one-time and annual application amounts for the most toxic element – nitrogen are calculated. It is indicated that in case of a deficiency of nutrients for phosphorus and potassium, an additional calculation for the mineral fertilizers introduction is carried out. Results. An example of calculating the annual amount of irrigation mixture for corn for silage when removing nutrients with an accepted harvest of green mass of 500 q/ha is provided. The calculation is determined by: application rate, cubic meters/ha; nitrogen content in the application rate, kg/ha; the annual volume of the irrigation mixture, with a nitrogen content of 0.15 %. In the example, the calculation is performed for the possible presence of fertilizers in cattle drains according to two variants of technological schemes: without using a mixer, when introducing fertilizers from the storage tank directly into the suction pipeline; using a mixer, when introducing fertilizers from the storage tank into the suction pipe of the mixer. For the calculation, the initial data of hydraulic parameters are given, the consumption of cattle manure with a humidity of 92–95 % is taken as the main calculation parameter. Conclusions: the developed theoretical calculation of the system for introducing organic fertilizers into the suction pipelines of pumping stations allows determining the rate of one-time and annual fertilizer application and determining the hydraulic parameters of the fertilizer input system without a jet mixer.